Introduction of a mobile application platform as a decision support tool to enhance antimicrobial stewardship: an experience from the United Arab Emirates - O’Sullivan, Siobhán; Shamseddine, Jinan; Sadeq, Ahmed; Ali, Rizwan; Yousuf, Khadija; Naqbi, Aisha Al; Alakhras, Abdullah; Foroodi, Farindokht; Jabeen, Fouzia; Nsutebu, Emmanuel; Hantouche, Mireille; Everett, Dean; et al. (Frontiers in Tropical Diseases, 2023)
Antimicrobial resistance, mainly driven by inappropriate antibiotic use, is a global threat to health, requiring strategies to optimize antimicrobial usage. Antimicrobial stewardship (AMS) programs in hospitals are designed to optimize the use of antibiotics to effectively treat infections, protect patients from harmful side effects associated with unnecessary exposure, and reduce the risks of antimicrobial resistance emergence. Educating clinicians through antimicrobial guidelines has been a key function of AMS programs. However, monitoring access and utilization of printed booklets or intranet-hosted guidelines is complex and may not provide helpful feedback to the AMS leadership regarding their uptake by clinicians. Sheik Shakhbout Medical City, in partnership with Mayo Clinic, is the first hospital in the United Arab Emirates to adopt a mobile application platform for antimicrobial guidance and clinical decision support, including tailored antimicrobial choices based on local and national antibiograms and formulary. We describe the journey to adopt a mobile application platform, content development, migration, and roll-out and evaluate its impact through descriptive analysis of user statistics.